2001
DOI: 10.1097/00001888-200105000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Why Physicians Are Unprepared to Treat Patients Who Have Alcohol- and Drug-related Disorders

Abstract: Most primary care physicians do not feel competent to treat alcohol- and drug-related disorders. Physicians generally do not like to work with patients with these disorders and do not find treating them rewarding. Despite large numbers of such patients, the diagnosis and treatment of alcohol- and drug-related disorders are generally considered peripheral to or outside medical matters and ultimately outside medical education. There is substantial evidence that physicians fail even to identify a large percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
191
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(208 citation statements)
references
References 28 publications
3
191
0
5
Order By: Relevance
“…Several physicians reported that they were uninterested in providing treatment for their patients' addictive disorders. This lack of interest was linked with a negative characterization of addicted patients and supports previous research on physicians' and clinic directors' attitudes on treating addicted patients [19][20][21] . Some of these attitudes seem to result from physicians feeling unprepared to treat addiction.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Several physicians reported that they were uninterested in providing treatment for their patients' addictive disorders. This lack of interest was linked with a negative characterization of addicted patients and supports previous research on physicians' and clinic directors' attitudes on treating addicted patients [19][20][21] . Some of these attitudes seem to result from physicians feeling unprepared to treat addiction.…”
Section: Discussionsupporting
confidence: 81%
“…This finding reinforces previous research on physicians' attitudes regarding their training in substancerelated disorders 22,23 , highlights the need for improved training in addiction at the medical school and post-graduate levels, and suggests potential issues and areas of concern that might be more fully explored in the 8-h training program designed to prepare physicians who are interested in providing buprenorphine treatment. Our data suggest that the following topics might be important to address: (1) the research and practice evidence that supports the appropriateness of officebased addiction treatment [19][20][21]24 , (some respondents viewed addiction treatment as outside their realm of medicine); (2) when and how to seek guidance on patient care (some physicians expressed concerned about treating addiction without access to specialists). Our experience indicates that having support from buprenorphine providers (on-site, by phone or email) is often sufficient 25 ; (3) strategies for working with "difficult-to-treat" patients-(the majority of the difficulties reported by physicians related to discomfort in setting appropriate boundaries); (4) treatment of co-existing disorders (many physicians expressed concern about their competence in treating medical and psychiatric problems associated with opioid dependence).…”
Section: Discussionmentioning
confidence: 99%
“…Third, training in substance abuse and pain management is lacking in medical school and residency, and the subtleties of UDT interpretation are omitted from standard curricula. [35][36][37][38][39][40] Physician overconfidence can lead to diagnostic errors, 32 in this case leading to either under-diagnosis or over-diagnosis of abuse or diversion, with potentially negative consequences for patients. 18 One way overconfidence can cause diagnostic error is through premature closure, for example, concluding without further investigation that an opiate-positive urine drug screen reflects a patient's prescribed oxycodone use.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown lack of knowledge among medical students and attitudes that could interfere with their care for patients with abuse problems as well as their own wellbeing (16,17). Factors found to contribute to the students' knowledge and attitudes include previous experience with substance use, family history, social and cultural context and exposure to drug education programmes (18). Researchers have highlighted the role of medical education in ensuring that doctors become competent in managing patients with substance abuse.…”
Section: Introductionmentioning
confidence: 99%